The evolutionay and clilnical impllications of the uneven distribution of the frequency of the inherited haemoglobin variants over short geographical distances - Premawardhena, A; Allen, A; Piel, F; Fisher, C; Perera, L; Rodrigo, R; Goonathilaka, G; Ramees, L; Peto, T; Olivieri, N; Weatherall, D (Wiley, 2016)
Studies of the frequency of heterozygous carriers for common inherited diseases of haemoglobin in over 7500 adolescent children in 25 districts in Sri Lanka have disclosed a highly significant variation over very short geographical distances. A further analysis of these findings, including their relationship to the past frequency and distribution of malaria, climatic variation, altitude, ethnic origin and consanguinity rates, have provided evidence regarding the evolutionary basis for the variable distribution of these conditions over short distances. It is likely that the complex interplay between malaria and the environment, together with related ethnic and social issues, exists in many countries across the tropical belt. Hence, these observations emphasise the importance of micromapping heterozygote distributions in high-frequency countries in order to define their true burden and the facilities required for the prevention and management of the homozygous and compound heterozygous disorders that result from their interaction.